STRUCTURE-BASED DOCKING STUDIES TOWARD EXPLORING THE POTENTIAL ANTICANCER ACTIVITY OF MORIN AGAINST NON-MELANOMA SKIN CANCER THERAPEUTIC DRUG TARGETS - C, Anjugam; M, Sridevi; Ts, Gnanendra (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The purpose of this study is to explore the anticancer activity of morin compound against human cyclooxygenase-2 (COX-2) and peroxisome-proliferator-activated receptors (PPARs) isotypes (PPARα and PPARγ) through in silico molecular docking studies. Methods: The 3D structures of human COX-2 complexed with ibuprofen (PDB ID: 4PH9), PPARα complexed with a synthetic agonist (2S)-2-(4- methoxy-3-{[(pyren-1-yl carbonyl) amino] methyl} benzyl) butanoic acid (PDB ID: 3VI8) and PPARγ complexed indomethacin (PDB ID: 3ADX) were retrieved from protein databank. The cocrystallized sites were considered as binding sites, and the docking with morin compound was performed along with their respective cocrystals for each target and compared their interactions and binding affinities. Results: It is observed that the morin compound exhibited better binding energy of -32.9528 kJ/mol against PPARα followed by COX-2 (binding energy: −18.4311 kJ/mol) and PPARγ (binding energy: −17.4228 kJ/mol) when compared to their cocrystallized ligands. Conclusion: The present study suggests that morin compound might serve as potential alternatives in the prevention of skin cancers by showing better activity against PPARα.